South Asian Children Have Increased Body Fat in Comparison to White Children at the Same Body Mass Index - Emma L. J. Eyre; Michael J. Duncan; Alan Nevill (Children, 2017)
The ability of body mass index (BMI) to predict excess fat in South Asian children is unknown. This cross-sectional study examines the influence of ethnicity on body fatness in children. Weight status and body fat were determined using BMI, waist circumference (WC), two skinfold sites (SF; triceps and subscapula) and leg-to-leg bioelectrical impedance analysis (BIA; Tanita BF350, Tanita, Tokyo, Japan) in 194 children aged 8.47 ± 0.50 years from Coventry, United Kingdom. Biological maturity was also determined. Analysis of covariance (ANCOVA) identified significant differences between ethnic (p < 0.001) and gender groups’ BMI (p = 0.026), with a significant covariate for skinfold (p < 0.001) and bioelectrical impedance (p < 0.001). For a given body fat value, South Asian children and females had a lower BMI value (−1.12 kg/m2, p < 0.001 and −0.50 kg/m2, p = 0.026, respectively, when adjusted for SF; −1.56 kg/m2, p < 0.001 and −0.31 kg/m2, p = 0.16, respectively, when adjusted for BIA) compared with white children and boys. The prediction model including ethnicity, gender and BIA explained 80.4% of the variance in BMI. Maturation was not found to be a significant covariate (p > 0.05). To conclude, the findings suggest that BMI cut-points may need to be lowered in South Asian children, and thus age-by-sex-by-ethnicity specific BMI cut-points are needed in children. Further research examining body composition with health parameters in this population is needed.